2017
DOI: 10.1016/j.neuroimage.2017.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multiple tau-PET measures as biomarkers in aging and Alzheimer's disease

Abstract: The recent development of tau-specific positron emission tomography (PET) tracers enables in vivo quantification of regional tau pathology, one of the key lesions in Alzheimer's disease (AD). Tau PET imaging may become a useful biomarker for clinical diagnosis and tracking of disease progression but there is no consensus yet on how tau PET signal is best quantified. The goal of the current study was to evaluate multiple whole-brain and region-specific approaches to detect clinically relevant tau PET signal. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
422
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 379 publications
(448 citation statements)
references
References 54 publications
21
422
4
1
Order By: Relevance
“…the subject component score for IC-5) rather than using three separate numbers for each Braak ROI. This observation may explain why Braak ROIs do not outperform global measures of τ-PET (Maass et al, 2017). The other components do not meet these criteria and are referred to as atypical, or ‘non-Braak-like’ patterns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the subject component score for IC-5) rather than using three separate numbers for each Braak ROI. This observation may explain why Braak ROIs do not outperform global measures of τ-PET (Maass et al, 2017). The other components do not meet these criteria and are referred to as atypical, or ‘non-Braak-like’ patterns.…”
Section: Resultsmentioning
confidence: 99%
“…While this may not necessarily indicate that the signal simultaneously becomes abnormal in all of these regions, it does argue against a sequential involvement of Braak regions with limbic structures becoming involved before neocortical regions, as one would expect from a seed-based templating mechanism following the Braak staging gradient. Sequential spreading not fully detected by τ-PET until later stages could also produce these observations, but using Braak-staging ROIs, or any other regional approach, would not confer any particular advantage over global measures in such a case (Maass et al, 2017). The lack of utility in using Braak-staging ROIs is also highlighted by the fact that the τ-PET signal in preclinical AD is more widespread than predicted by pathologic staging as was recently shown by others (Mishra et al, 2017) and also observed in this study (see Figure 6 and Supplementary Figures 11–13).…”
Section: Discussionmentioning
confidence: 99%
“…Quality control of the output was carried out. The thickness of the entorhinal cortex was selected in this study as a measure of medial temporal atrophy, based on previous findings with another tau PET tracer [40] showing that entorhinal thickness rather than hippocampal volumes is more closely related to local tau PET tracer binding.…”
Section: Methodsmentioning
confidence: 99%
“…A cutoff value of 1.5 was used to define positive binding voxel on SUVP, representing 1.5 times SD from whole brain mode. For comparison, SUVR PBP was also calculated by using previous published cutoff values, 1.5 for THK5351 PET and 1.19 for AV1451 PET [1316]. The acquisition and reconstruction of THK5351 scans were identical as in the papers that report the cut-off values, and more or less similar for AV1451.…”
Section: Methodsmentioning
confidence: 99%